Fatal sepsis associated with a storage container leak permitting platelet contamination with environmental bacteria after pathogen reduction. Issue 2 (8th December 2020) - Fadeyi, Emmanuel A.; Wagner, Stephen J.; Goldberg, Corinne; Lu, Thea; Young, Pampee; Bringmann, Peter W.; Meier, Nathaniel M; Namen, Andrew M.; Benjamin, Richard J.; Palavecino, Elizabeth
Abstract: Background: Pathogen reduction technology and enhanced bacterial culture screening promise to significantly reduce the risk of transfusion‐associated septic reactions due to contaminated platelets. Recent reports suggest that these interventions lack efficacy for post‐collection and processing contamination with environmental organisms if the storage bag integrity is compromised. Case Report: We report a fatal septic transfusion reaction in a 63‐year‐old patient with chronic kidney and liver disease who received a pathogen reduced platelet transfusion in anticipation of surgery. Methods: The residual platelet concentrate was cultured, with the detected microorganisms undergoing 16S genotype sequencing. Separate pathogen reduction studies were performed on the recovered bacteria, including assessment for amotosalen photoproducts. The storage container was subjected to pressure testing and microscopic examination. Environmental culture screening was performed at the hospital. Results: Gram negative rods were detected in the platelet unit and cultures of both platelet component and the patient's blood grew Acinetobacter baumannii complex, Leclercia adecarboxylata and Staphylococcus saprophyticus. These strains were effectively inactivated with >7.2, 7.7, and >7.1 log10 kill, respectively. The platelet storage container revealed a leak visible only on pressure testing. Hospital environmental cultures were negative and the contamination source is unknown. A. baumannii complex and S. saprophyticus 16S genotyping sequences were identical to those implicated in a previously reported septic reaction. Conclusion: Findings are compatible with post‐processing environmental contamination of a pathogen reduced platelet concentrate via a non‐visible, acquired storage container leak. Efforts are warranted to actively prevent damage to, and detect defects in, platelet storage containers, and to store and transport components in clean environments.